Desulphurization of coals of different ranks in the presence of slimes by reverse flotation. (November 2019) - Zhou, You; Albijanic, Boris; Tadesse, Bogale; Wang, Yuling; Yang, Jianguo; Zhu, Xiangnan
Abstract: In this paper, the flotation separation of pyrite from sub-bituminous and meta-bituminous coals in the presence of slimes was investigated. The sub-bituminous coal and the meta-bituminous coal have significant differences in their surface properties compared with pyrite. The flotation experiments were performed in the presence of potassium amyl xanthate (PAX) collector. The adsorption of PAX on pyrite was significant while that on the coal surfaces was negligible. The recovery of pyrite from sub-bituminous coal increased by 55% when the concentration of PAX increased from 1 × 10 − 4 mol/L to 5 × 10 − 4 mol/L. Similarly, pyrite recovery from the meta-bituminous coal increased by up to 60% for the coarser size fraction upon increasing PAX concentration from 1 × 10 − 4 mol/L to 5 × 10 − 4 mol/L. Before the de-sliming process, the flotation recovery of pyrite increased with decreasing coal particle size whereas the opposite is true for pyrite grade. Desliming reduced the adsorption amount of PAX on pyrite by more than 50% because of the removal of fine particles that would otherwise be available for adsorption. Desulphurization of fine coal appears to be challenging probably due to the increased entrainment of fine coal particles during pyrite flotation. The de-sliming process increased pyrite grade by >20% for the meta-bituminous coal and by 10% for the sub-bituminous coal. The results suggest that excessive collector consumption by fine particles and slimes, and entrainment are the main challenges in separating pyrite from coal particles. Highlights: Desulphurization of coals by flotation in the presence of slimes was investigated. Higher collector adsorption on particles was observed in the presence of slimes. De-sliming significantly increased pyrite recovery from coals of different ranks. Slimes lead to higher collector consumption and reduced pyrite grade.